PENGARUH FRAKSI VOLUME TERHADAP KEKUATAN MEKANIK PADA KOMPOSIT BERPENGUAT SERAT POHON TERAP MENGGUNAKAN RESIN POLYSTER BQTN-157 - Abdullah hamid; Masdani Masdani; Idiar Idiar (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Composite is a system composed by mixing two or more different materials, in form and composition. Between two or more materials are insoluble in each other. Composites are very influential on the mechanical properties. The most influential factors are fiber fraction, fiber length and immersion used. This study aims to examine the effect of volume fraction variations on the mechanical properties of applied tree bark fiber reinforced composites. This study used matrix and fiber volume fraction 5% : 95%, 6% : 94%, 7% : 93% with 5% NaOH for 2 hours. The material used is fiber. Applied tree bark. Composites are made using the hand lay up method. The tests carried out were tensile test and Impact Charpy test with ASTM D638 Type 1 tensile test standard and ISO-179 impact test. The result of the highest tensile strength at 7% volume fraction that is equal to 36.32 Mpa. While the results of the smallest tensile strength at 5% volume fraction that is equal to 28.74 Mpa. And the results of the highest composite impact test at 7% volume fraction that is 0.051198 Joul/mm2. Meanwhile, the lowest impact strength was at 5% volume fraction with a value of 0.009652 Joul/mm2.